Topoisomerase II as a target for anticancer drugs: When enzymes stop being nice - Fortune, John M.; Osheroff, Neil (Progress in Nucleic Acid Research and Molecular Biology, 2000)
Topoisomerase 11 is an essential enzyme that plays a role in virtually every cellular DNA process. This enzyme interconverts different topological forms of DNA by passing one nucleic acid segment through a transient double-stranded break generated in a second segment. By virtue of its double-stranded DNA passage reaction, topoisomerase 11 is able to regulate DNA over- and underwinding, and can resolve knots and tangles in the genetic material. Beyond the critical physiological functions of the eukaryotic enzyme, topoisomerase 11 is the target for some of the most successful anticancer drugs used to treat human malignancies. These agents are referred to as topoisomerase 11 poisons, because they transform the enzyme into a potent cellular toxin. Topoisomerase 11 poisons act by increasing the concentration of covalent enzyme-cleaved DNA complexes that normally are fleeting intermediates in the catalytic cycle of topoisomerase 11. As a result of their action, these drugs generate high levels of enzyme-mediated breaks in the genetic material of treated cells and ultimately trigger cell death pathways. Topoisomerase 11 is also the target for a second category of drugs referred to as catalytic inhibitors. Compounds in this category prevent topoisomerase II from carrying out its required physiological functions. Drugs from both categories vary widely in their mechanisms of actions. This review focuses on topoisomerase 11 function and how drugs alter the catalytic cycle of this important enzyme.